DC motor over speed indicator / Muhammad Najmi Farid Wajdee & Nurshahirah Athirah Rohman - Wajdee, Muhammad Najmi; Rohman, Nurshahirah Athirah (2015)
This project is designed for indicating over-speed and direction of rotation of the motor used in mini hand tools, water pump motors, toys and other appliances for DC motor. DC motor over speed indicator circuit is a circuit that constantly monitors the condition of the speed. When in forward rotation the yellow LED will light on, and during in reverse rotation the green LED will light on. Over speed happened is due to voltage increasing in de motor, so that when over speed happen the red LED light on and the Piezo Buzzer will sound. The reason why an interest to work on this project has been developed is because of people don't know there is natural change in speed due change in load that make the device in over speed limit on the shaft. Besides, the speed control is done manually by some of automatic control device, so the percentage of injuries will getting higher. The immediate objective of this research project are to improve the safety of DC motor equipment. Besides, to reduce the number of accidents or injury in using DC motor equipment. In order to solve this problem, we choose 'DC Motor Over Speed Indicator'.